Views of Post Graduate Social Studies Students, University of Jos on Factors Militating against Patriotic Nigeria Citizens - Ariya, Dauda A. (NIU Journal of Humanities, 2020)
This study examined the views of post graduate social studies education students of University of Jos on the factors militating against patriotic Nigeria citizens. Patriotism has been perceived as a key attribute to developing a nation and most developed nation are basking on the gains of patriots while underdeveloped nations remain in the shaft because absent of patriots or insignificant amount of patriots. In the case of Nigeria, patriotism is pertinent and a lot of hurdles happen to be hindering the patriotic zeal which the study investigated. In line with that, three objectives were formulated for the study and three corresponding research question were equally posted. The research design adopted for the study was a survey specifically cross sectional survey and the population was same as sample which consisted of 37 post graduate social studies education students for academic session 2018/2019. Zero sampling technique was used while structured questionnaire was developed for data collection. The data collected were analyzed using simple percentage where the analysis revealed that, corruption, religion and ethnicity happen to be the major factors affecting patriotism amongst Nigeria citizens and if addressed squarely Nigeria can have more and lot more patriots. The study recommended among others that, sensitization should be highly encouraged, ethnic and religious leaders should preach loyalty to the state against preaching loyalty to ethnicity or any other affiliation and also attitudinal change should highly be prioritize from the family level where right values and patriotic attitudes will be instill on the young ones for sustainable growth and national rebirth. Keywords: Patriotism, Citizens, Ethnicity, Religion, Social Studies Students